Evaluation of Abram’s Needle Pleural Biopsy Verses Pleuroscopic Biopsy at Tertiary Care Hospital - Jawaid Hussain Memon, Uzma Bukhari, Saleem Sadiq, Nadeem Ahmed Rizvi (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2014)
Objective: To evaluate the diagnostic yield of Abram’s needle pleural biopsy verses Pleuroscopic biopsy. Study Design: Observational, descriptive study. Place and Duration: The work was completed in two years duration in the department of Pathology, Basic Medical Sciences Institute and Department of Thoracic Medicine, Jinnah Postgraduates Medical Centre, Karachi. Material and Methods: A total of 36 pleural biopsies were received during study period. The material was obtained by Abram’s needle biopsy and Pleuroscopic biopsy to see the accuracy of both procedures. After processing of all the specimens the H & E stained slides were made and examined under light microscope to determine the various non-neoplastic and neoplastic lesions. Special stains such as PAS, PAS-D, Trichrome and Reticulin were also employed in some cases for a definitive diagnosis. Results: According to the type of biopsy technique, a total of 36 samples of pleural biopsy were received. Among these 36 cases, neoplastic and non- neoplastic pleural biopsy lesions showed diagnostic yield with Abram’s biopsy to be 13 (36.12%) cases and 14 (38.88%) cases respectively, 09 (25%) cases were inconclusive. The neoplastic and non- neoplastic pleural biopsy lesions showed diagnostic yield with Pleuroscopic biopsy 17 (47.20%) and 15 (41.60%) cases respectively. Four 04 (11.27%) cases were inconclusive. Out of 36 cases, 21 (58.3%) were male, and a higher diagnostic yield was seen more in the 4th decade. Conclusion: Diagnostic yield with Pleuroscopic biopsy was high as compared to Abram’s needle biopsy.